Anthelmintic and antibacterial studies of zinc oxide NPs: Synthesized using dragon fruit juice as novel fuel. (2021) - Puttaraju, T.D.; Manjunatha, M.; Maruti, G.; Srinivasan, Vani; Haseen Buvabi, Syeda; Bharathi, T.R.
Abstract: Present study focus on the dragon fruit as a novel fuel in the field of green synthesis. It is the best-known source to get a variety of natural antioxidants like flavonoids, hydroxycinnamates and betalains. In this context, the High-temperature solution combustion method is used to produce nanoparticles of zinc oxide materials (ZnO-NPs) by zinc nitrate as a starting material and dragon fruit juice used as a fuel. The ZnO-NPs were identified by XRD, Fourier transform infrared spectroscopy (FTIR), SEM & TEM. Wurtzite crystal structure was confirmed by XRD and the average crystallite size was found to be 42 nm. The prepared ZnO.-NPs presented significant anthelmintic property against Indian earthworms in CMC (Carboxymethyl cellulose) solution. Prepared ZnO-NPs from dragon fruit juice exhibited very good antimicrobial property against different bacterial strains such as Bacillus Subtilis ATCC 19659 and Salmonella Typhimurium ATCC 23564.